Risk Sharing, Sharecropping and Uncertain Labour Markets - Newbery, David M. G. (Review of Economic Studies, 1977)
Journal Article Risk Sharing, Sharecropping and Uncertain Labour Markets Get access David M. G. Newbery David M. G. Newbery Churchill College, Cambridge, and Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 3, October 1977, Pages 585–594, https://doi.org/10.2307/2296910 Published: 01 October 1977 Article history Received: 01 May 1974 Accepted: 01 December 1976 Published: 01 October 1977